Determinants of Type 2 Diabetes Mellitus among Adults in Urban and Rural Areas of Sragen Regency, Central Java, Indonesia - Novia Erliana Wandansari; Ika Sumiyarsi Sukamto; Setyo Sri Rahardjo; Erindra Budi Cahyanto; Revi Gama Hatta Novika (Masters Program in Public Health, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a non-communicable disease with increasing prevalence in both urban and rural areas. Differences in sociodemographic characteristics and health behaviors between urban and rural populations are suspected to influence the clinical profile and demographic characteristics of T2DM patients. This study aims to analyze differences in T2DM patient characteristics in adults in urban and rural areas of Sragen Regency, Indonesia, and identify the most dominant factors differentiating these two groups. Subjects and Method: This was a comparative observational analytical study with a cross-sectional design conducted in six health centers in Sragen Regency representing urban and rural areas. Research subjects were adult patients with T2DM who met inclusion criteria. Variables examined included age, sex, educational level, income, occupation, and physical activity. Data were collected using structured questionnaires and medical records. Bivariate analysis was performed using the Chi-square test, while multivariate analysis used binary logistic regression. Results: Significant differences were found between T2DM patients in urban and rural areas based on age (p=0.035), educational level (p=0.007), income (p=0.011), occupation (p=0.016), and physical activity (p=0.005). No significant difference was found in sex distribution between the two areas (p=0.078). Binary logistic regression analysis showed that physical activity was the most dominant factor differentiating T2DM patient characteristics in urban and rural areas (OR=2.326; p=0.007). Patients with low physical activity had 2.326 times higher odds of residing in urban areas compared to those with moderate or high physical activity. Conclusion: Physical activity is the most dominant factor differentiating T2DM patient characteristics between urban and rural areas. Area-specific T2DM prevention and control strategies should prioritize physical activity improvement with approaches tailored to local community characteristics.